Simulation of DC Buck Converter for Battery Charger using MATLAB Simulink - Alias, Muhammad Azri; Ahmad, Md. Zarafi (Evolution in Electrical and Electronic Engineering, 2023)
This project is conducted to analyze the performance of a DC buck converter as well as other electronic components such as a rectifier used for a battery charger using MATLAB Simulink. The objective of the study was to determine the current output while optimizing the rate of charger and efficiency of the buck converter during the charger process. The simulation model was developed based on a block of electronic components as the foundation for the simulation development. It includes components such as a capacitor, inductor, diode and switch along with control signals for controlling the current and voltage output desired. The simulation scenarios included various charger conditions such as types of switches used, the value of an inductor, and additional components added in the simulation to be analyzed and compared in order to get the highest effectiveness.  The results from the simulation demonstrate the effectiveness of the buck converter in aspects of getting a stable output voltage and regulating the charger current. The converter results in low current ripple and voltage ripple indicating a smooth charging procedure. The effectiveness of the buck converter was evaluated as well as the rectifier and highlighting the ability of the buck converter to convert input voltage (VAC) to charging output voltage (VDC) effectively. Overall, the simulation of the DC Buck converter as a battery charger using MATLAB Simulink shows a comprehensive analysis based on the performance of the converter as a battery charger. The findings from this project can contribute to the future design and implementation of efficient and reliable battery charger systems on a daily basis.